Is the user's experience to blame? The rise and fall of Bluegogo - Xu, Jingyue, (SAGE Business Cases., 2018)
Due to fierce competition in the burgeoning bike-sharing market, Bluegogo, once known as "the best user-friendly shared bikes" in China, came to a deadlock for lack of capital. It was later purchased by Didi and went back into the market. And yet its prospect is still blurry, given a number of severe challenges. This case studies the rise and fall of Bluegogo from the perspective of the competitive strategy for burgeoning industries. And in particular, the focus is on three essential factors: selection of a target group, identification of customer needs, and optimization of customer service. It will help students comprehend the impact of the peculiarities of burgeoning industries on a company's competitive strategy.